Rancang Bangun Integrated Management Library System (IMAGIN) Menggunakan Metode Waterfall berbasis Progressive Web App (PWA) - Nasrullah, Muhammad; Ramadhani Wijaya, Pratama; Insani, Rokhmatul; Anaking, Purnama (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2025)
The development of science and technology (IPTEK) is currently experiencing very rapid progress, one of which is seen from the emergence of a digital library information system. The Integrated Management Library System (IMAGIN) is equipped with various features, including e-catalogs. the ability to download, as well as a home page display that can be accessed directly from the device's main screen and the Progressive Web App (PWA) feature. The development of the IMAGIN system so that it can be accessed offline and is based on a mobile application using PWA. The implementation results show that with Service Worker technology and App Shell Architecture, the system can run offline and is compatible with mobile devices. Testing using Edge DevTool Testing and Black Box Testing proved that there were no Errors or Bugs, so this system was declared successfully developed into a PWA-based website.